Advantages of BioMatrix respiratory gating in free-breathing three-dimensional magnetic resonance cholangiopancreatography: a prospective comparative study - Qing Yang; Xueyi Ding; Qiuyang Guo; Yifan Tang; Jianyu Lin; Yantu Huang; Mengxiao Liu; Junqiang Lei (Insights into Imaging, 2025)
Abstract Objectives To compare the image acquisition time, total examination time, image quality, and technical reliability of three free-breathing MRCP techniques: BioMatrix-triggered (BM-MRCP), respiratory-gating triggered using respiratory bellows (RG-MRCP), and navigator-triggered (NT-MRCP). Methods A prospective intra-individual comparison was performed in 47 patients undergoing 3.0-T MRCP for suspected pancreatic and biliary diseases. Two patients with technique adaptability limitations were included in the reliability analysis as “technical failures.” For primary analyses, data from 45 patients completing all three techniques were used. Image quality was evaluated by three blinded radiologists (experience: 5, 10, 16 years). Statistical analysis included Friedman tests with Bonferroni correction (p < 0.0167). Results Median total examination times were significantly shorter for BM-MRCP (218 [48] seconds) compared to RG-MRCP (228 [56] seconds) and NT-MRCP (259 [53] seconds) (p < 0.05). BM-MRCP and RG-MRCP had comparable image acquisition times, both significantly faster than NT-MRCP (p < 0.05). BM-MRCP provided superior image quality for key anatomical structures (p < 0.05), higher SNR, and CNR compared to RG-MRCP and NT-MRCP (p < 0.05). Image contrast showed no significant differences (p > 0.05). Two patients experienced failures with RG-MRCP or NT-MRCP due to breathing issues, while BM-MRCP had no failures. Conclusion BM-MRCP significantly reduces examination times while achieving superior image quality and technical reliability. Its integration into clinical workflows enhances efficiency, reduces technician workload, and improves patient-centered imaging. Critical relevance statement BioMatrix-gating 3D-MRCP enhances imaging efficiency and diagnostic accuracy for the biliary and pancreatic duct systems. By reducing scan times and improving workflow, it supports patient comfort and compliance. Its simplicity and reliability also make it ideal for high-throughput clinical settings. Key Points BioMatrix-triggered (BM)-MRCP shortens examination time, aiding patients with compliance or limitations. BM-MRCP offers superior image quality with reduced motion artifacts and higher clarity. BM respiratory sensors streamline workflows, boost reliability, and enhance patient comfort. Graphical Abstract